Organizational Citizenship Behavior of Islamic Banks through Meaning in Life and Meaning of Work - Heru Sulistyo (Jurnal Keuangan dan Perbankan, 2017)
Islamic banking had a market share that is still low if compared with conventional banks, so it has a big challenge to improve performance and competitive advantage. Employees who were willing to have extra work for their organization will lead to the improvement of their performance and their organization. Several studies have examined multiple factors that affect organizational citizenship behavior (OCB), but it was still slightly stressing on the importance of psychological aspects of meaning in life and the meaning of work. The purpose of this study was to examine the importance of meaning in life and the meaning of work factors in improving OCB in the organization. The sample in this study was employees of the Islamic banks in Central Java, amounted to 100 people. The data collections were conducted using questionnaires and in-depth interviews. Meanwhile, to analyze the data, the structural equation model with a Partial least squares software was used. The results of data analysis showed that meaning in life had a significant effect on satisfaction and organizational citizenship behavior. Meaning of work also had a significant effect on satisfaction and organizational citizenship behavior. An employee’s job satisfaction significantly affects the improvement of organizational citizenship behavior.DOI: https://doi.org/10.26905/jkdp.v21i4.1407